Removal of sodium diclofenac from aqueous solution by adsorption using activated carbon prepared from cocoa pod husk as a low cost adsorbent characterization, optimization, kinetics and isotherms studies - Murniati (2013)
Cocoa pod husk (CPH) modified onto activated carbon as a low cost adsorbent was effective for removal of sodium diclofenac (SD) from aqueous solution by adsorption. SEM, EDX, and FTR were used to investigate the characteristics of raw material and activated carbon. The effects of various pH (3, 5, 7, 9, and 11), initial [SD] concentration (10, 15, 20, 25,, and 30 mg/L), CPH dosage (0.25, 0.5, 0.75, 1.0 and 1.25 g) and contact time (15, 30, 45, 60 and 75 min) were investigated. The results showed that by minimize pH and CPH dosage, and maximize the initial [SD] concentration, the percentage of SD removal increased accordingly. The percentages removal SD was varying from 76 to 93.6%. Central Composite Design (CCD) with response surface methodology (RSM) from Design Expert 7.0 software was used to evaluate the data and estimate the optimum condition. The optimum condition was achieved at pH 7, 30 mg/L of initial [SD] concentration, and 0.25 g of CPH dosage and 15 min of contact time. The equilibrium time was tested using pseudo-first-order, pseudo-second-order and intraparticle diffusion models. Kinetic studies showed that the adsorption followed pseudo-second-order reaction with the coefficient correlation value is 0.99998. The equilibrium data were analyzed using three isotherm models (Langmuir, Freundlich and Temkin). The data are better fitted by the Freundlich isotherm (R2= 0.99707) as compared to Langmuir model and Temkin model.